Analisis Pengaruh Integrative Leadership Terhadap Organizational Justice, Employee Engagement Dan Organizational Citizenship Behavior - Veronika Agustini Srimulyani (Universitas Airlangga, 2016)
Organizations have long been interested in how employees think and feel his work and what causes employees are willing to dedicate themselves to the organization. The researchers found a variable motivational leadership style that leads to the formation of positive attitudes of the officials who in turn can improve employee job performance. The objective of this research are to study the effect integrative leadership on organizational justice, employee engagement, and organizational citizenship behavior (OCB), with teachers at SMA/SMK/MAN/MAS di kota Madiun as respondents. This research used the quantitative approach with the survey method. The samples of this research were 409 teachers, selected non-randomly. The data were obtained by distributing questionnaires and analyzed by using the descriptive statistics and path analysis in inferential statistics. The results of the research can be concluded that: integrative leadership has a positive significant effect on organizational justice; integrative leadership significant positive effect on employee engagement; integrative leadership significant positive effect on employee engagement on OCB.